2020
DOI: 10.20473/mog.v28i22020.75-78
|View full text |Cite
|
Sign up to set email alerts
|

Profile study of ectopic pregnancy at Department of Obstetrics and Gynecology, Dr. Soetomo Hospital, Surabaya, Indonesia

Abstract: Objective: Ectopic pregnancy is a leading cause of maternal death during the first trimester of pregnancy, it can cause infertility and even death as a result of massive bleeding of the mother. Based on those fact, study of ectopic pregnancy is needed.Materials and Methods: This study used retrospective design and total sampling to collect the data and present it as a descriptive – analytical result.Results: Of the 98 samples, as many as 30.6% of the patients age was in the range of 26 - 30 years, there was 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Of the 98 samples, 30,6% of the patients had a range of 26-30 years, the use of hormonal contraception was found more often than an intrauterine device, 7% of patients were repeat cases, 12,1% of patient had a history of surgery in the abdominal or pelvic area, and most ectopic pregnancies were found in the first pregnancy and as many as 26,4% of patient accompained by aggravating infection. 14 Women with an ectopic pregnancy will complain of pelvic pain, but not all ectopic pregnancies will have this feature. Women of reproductive age who complain of pelvic pain, abdominal pain, nausea/vomiting, dizziness, and vaginal bleeding should be determined whether the patient is pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 98 samples, 30,6% of the patients had a range of 26-30 years, the use of hormonal contraception was found more often than an intrauterine device, 7% of patients were repeat cases, 12,1% of patient had a history of surgery in the abdominal or pelvic area, and most ectopic pregnancies were found in the first pregnancy and as many as 26,4% of patient accompained by aggravating infection. 14 Women with an ectopic pregnancy will complain of pelvic pain, but not all ectopic pregnancies will have this feature. Women of reproductive age who complain of pelvic pain, abdominal pain, nausea/vomiting, dizziness, and vaginal bleeding should be determined whether the patient is pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…1,11,12 In this case, the patient underwent a curettage procedure for her miscarriage history, which, although rare, had previously been recorded as a risk factor of ectopic pregnancy. 9 The diagnosis can then be confi rmed with positive serum β-hCG levels and ultrasound. Transvaginal ultrasound may be used to diagnose ectopic pregnancy during 5-9 weeks GA, with positive signs such as a sac of gestation that contains a fetal pole and heartbeat in the adnexal structure.…”
Section: Discussionmentioning
confidence: 99%
“…8 Indonesia is a developing country with around 5 million live births annually, with ectopic pregnancy happening in approximately 60.000 pregnancies annually. 9 Our center, dr. Soetomo General Hospital is a tertiary-level referral hospital managing about 600 births in 2021. A previous study in our center found 98 patients with ectopic pregnancy in 2 years (2013-2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because ectopic pregnancies can be lifethreatening if the ectopic pregnancy is not treated properly, patients need to be treated as properly and quickly as possible with medication or surgery. [1][2][3][4] Ectopic pregnancy is a common occurrence in all women of reproductive age. Doctors should be aware of the possibility of ectopic pregnancy in female patients of reproductive age.…”
Section: Introductionmentioning
confidence: 99%